Overconfidence and gender equality in the labor market - Spencer Bastani; Thomas Giebe; Oliver Gürtler (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
Using a promotion signaling model in which wages are realistically shaped by market forces, we analyze how male overconfidence combined with competitive workplace incentives affects gender equality in the labor market. Our main result is that overconfident workers exert more effort to be promoted, which translates into a higher probability of promotion and superior wage growth. Interestingly, workers who are not overconfident have higher expected ability conditional on promotion than overconfident workers. However, overconfident workers accumulate more human capital through learning-by-doing and therefore have higher expected productivity. Because overconfident workers compete fiercely, they incur higher effort costs and discourage their colleagues, and we find that overconfidence can be either self-serving or self-defeating for the overconfident worker.
Keywords: C72; D91; J16; J24; M51; M52; 330; overconfidence; promotion; competition; gender gap; tournament; theory